Forage yield, chemical composition and morphogenesis of Brachiaria brizantha cv. Piatã under regrowth periods (Research, Society and Development, 2020)
With the objective to evaluate the effects of regrowth period (14, 21, 28, 35 and 42 days) on green dry matter yield (GDMY), chemical composition and morphogenetic and structural characteristics of Brachiaria brizantha cv. Piatã, was carried out an experiment under greenhouse with natural conditions of light and temperature. GDMY yields and regrowth, leaf blade length, and leaf lifespan rate increased consistently (P